Representasi Elemen-elemen Jurnalisme dalam Film Boston Strangler - Fitriani, Suci; Meilinda, Nora (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2024)
The existence of films is not only used as an entertainment medium. In film, there is information, both educational and persuasive, that can be used as a lesson. Educational information itself is usually packaged in historical or news films such as the Boston Strangler film which is based on true story around the 1960s by taking the perspective of two female journalists. This research aims to find out the representation of journalistic elements contained in films. The research method used is a qualitative method using Charles Sanders Pierce’s semiotic analysis based on three things, namely representation, object and interpretant. The results of this study revealed that there were eleven scenes that represented the elements of journalism in the Boston Strangler film. Each scene analyzed is able to show the character of journalists who are responsible for their profession and follow the existing elements of journalism.